The meaning and the finality of the “censures” and the irregularities in canon law - NYKIEL, KRZYSZTOF (Prawo Kanoniczne, 2017)
In this paper, the Author presents the competency of the Apostolic Penitentiary which extends to all occult or secret matters that are able to be solved in the internal forum and he is focusing on the meaning and the finality of the “censures” and the irregularities in canon law. All cases of censures "latae sententiae", when they are strictly such, that is, when they have been incurred "ipso facto" and have not been the object of a judicial sentence or of a declaration, can be dealt with in the internal Forum. Some censures can be remitted by the local Ordinary or by major Superiors of religious for their own subjects; others can be remitted only by the Apostolic See. They are pointed out and subsequently analyzed: the excommunication of one who sacrilegiously profanes the Consecrated Species (can. 1367); the excommunication of one who uses physical violence against the Roman Pontiff (can. 1370 § 1); the excommunication of a priest who absolves his own accomplice in sins against the VI Commandment (can. 1378 §1). This type of absolution not only incurs an excommunication for the priest who absolves; it is also intrinsically invalid (can. 977), except in the case of danger of death; the excommunication of a bishop who consecrates a bishop without a pontifical mandate. The bishop consecrated is also excommunicated (can. 1382); the excommunication for attempted sacred ordination of a woman and attempted reception of sacred orders by a woman; lastly, the excommunication of a confessor who directly violates the sacramental seal of confession (can. 1388). The author highlights that also the occult cases of irregularity, either for the reception of sacred orders or for their exercise, are dealt with in the internal forum. An irregularity is of its nature perpetual. It does not cease automatically but it can be dispensed. A simple impediment may cease automatically, e.g., a man’s wife dies, the impediment to ordination ceases. On the other hand, an impediment could be dispensed, e.g., when a married man is allowed ordination. The only irregularities or simple impediments now existing in the 1983 Code are those listed in the following canons. Irregularities which impede reception of orders: Amentia or other psychic illness (can. 1041, 1°); apostasy, heresy, or schism (can. 1041, 2°), attempted marriage (can. 1041, 3°); voluntary homicide or a completed abortion (can. 1041, 4°); self-mutilation or attempted suicide (can. 1041, 5°); act of orders reserved (can. 1041, 6°). Simple Impediments which impede the Reception of Orders: a man who has a wife (can. 1042, 1°); an office or administration forbidden to clerics (can. 1042, 2°); a neophyte (can. 1042, 3°). Lastly there are irregularities and impediments which affect those already in orders: orders received while being affected by an irregularity (can. 1044, §1, 1°); public apostasy, heresy or schism (can. 1044, §1, 2°); delict in can. 1041, nn. 3, 4, 5, 6; amentia or psychological infirmity (can. 1044, §2, 1°)